Eating disorders in pediatric population, analysis of some of the most common risk factors - Czeczotka, Magdalena; Skorupska, Marta; Popławska, Natalia Aleksandra; Śliz, Justyna; Woźniak, Krzysztof (Journal of Education, Health and Sport, 2024)
Introduction: This article reviews a number of studies that have sought to determine what are risk factors that may cause eating disorders in the pediatric population, taking into account the age and gender of the subjects. This study focuses on issues related to purging, bulimic behaviors, and psychological orthorexia and what impact the most common risk factors for these behaviors have in the pediatric population. Aim of study: The aim of the study is to present a comprehensive review of some of the most common risk factors predisposing to the development of eating disorders in the pediatric population, and how these factors have a direct impact on each other and are intertwined, by using available knowledge, paying particular attention to a new potential risk factor - social media. Materials and methods: Materials used in this study were found in the PubMed database, using the following keywords: , Social media”, , Mass media”, , Peers”, , Family”, , Orthorexia nervosa”, , Social media”, , Children”, , Adolescence”. Conclusion: Eating disorders are a growing problem. Our research focuses on potential risk factors, with the greatest emphasis on a relatively new risk factor: social media and screen time, and how these two factors influence young minds, what impact they have on the eating habits of children and adolescents, and what can be done to prevent eating disorders in the pediatric population.